2010
DOI: 10.1097/00004583-201004000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Demographic, and Familial Correlates of Bipolar Spectrum Disorders Among Offspring of Parents With Bipolar Disorder

Abstract: History of anxiety and/or disruptive behavior disorders, as well as presence of bi-lineal parental BP, is associated with elevated risk of bipolar spectrum disorders among offspring. If replicated prospectively, these findings could have implications for the diagnosis and treatment of psychopathology among BP offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 52 publications
4
29
0
5
Order By: Relevance
“…Correspondingly, two more recent studies performed by the team of the Pittsburgh Bipolar Offspring Study showed that subthreshold manic or hypomanic symptoms are an important diagnostic risk factor for subsequent onset of a manic, mixed or hypomanic episode onset . Also, major depressive episodes and disruptive disorders were found to be associated with BD conversion .…”
Section: Introductionmentioning
confidence: 91%
“…Correspondingly, two more recent studies performed by the team of the Pittsburgh Bipolar Offspring Study showed that subthreshold manic or hypomanic symptoms are an important diagnostic risk factor for subsequent onset of a manic, mixed or hypomanic episode onset . Also, major depressive episodes and disruptive disorders were found to be associated with BD conversion .…”
Section: Introductionmentioning
confidence: 91%
“…A recent meta‐analysis suggested that the most potent predictors were family history, an earlier age of onset and the presence of psychotic symptoms 574. There is an increased prevalence of BD among offspring of parents with BD 575, 576, 577. Although there is no uniform strategy for managing depression (or ADHD, anxiety, etc.)…”
Section: Specific Populationsmentioning
confidence: 99%
“…Probands often manifest symptoms of BD during adolescence and early adulthood . Longitudinal studies indicate that one of the most robust predictors of subsequent declaration of BD illness is early psychopathology with specific (ie mood symptoms) and/or non‐specific (ie attentional problems) features …”
Section: Introductionmentioning
confidence: 99%